Art and life oposition in the drama "Black Panther and the White Bear " by V.Vynnychenko and novel "Creativity" by E. Zola (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
«The opposition between art and life in Vynnychenko’s drama «Black Panther and White Bear» and E. Zola's novel «Creation». In the article the relevant problems in researching the European literature of the end of 19th – the first half of 20th century are examined. Works that are analysed: the «Black panther and White bear» by V. Vynnychenko and a novel by E. Zolya «Creation». The author compares texts by means of contextual and intertextual analysis.
Keywords: opposition; drama